Offshore renewable energy and nature conservation: the case of marine tidal turbines in Northern Ireland - Haslett, J; Garcia-Llorente, M; Harrison, P; Li, S; Berry, P (Springer Verlag, 2016)
The global demand for renewable energy continues to increase rapidly and with it the necessity to develop and test new technologies to deliver the power. Offshore renewable energy sources that harness wind, wave or tidal power are of major interest. Technological advances in these directions have not been matched by a clear understanding of the environmental impacts of the new devices, with most existing research concentrated on the impacts of offshore wind farms. Decisions often continue to be made without the support of a clear evidence base. Here we use an underwater tidal turbine, SeaGen, constructed and operated within the Strangford Lough marine protected area in Northern Ireland, as a case study to explore the potential impacts of the turbine as points of concern and argumentation in the decision-making processes. We use information obtained from official documents and one-to-one interviews with the main stakeholders. Our results demonstrate that during the construction and operation of the turbine the perceptions and views of different stakeholders sometimes disagreed but were often surprisingly similar in relation to both likelihood and intensity of the potential impacts of the turbine on marine biodiversity, ecosystem services and human well-being in general. The overall consensus of views was refined and evolved under an adaptive management approach over the 10 years of the discussions and decision-making processes. The results are discussed in relation to cumulative gains in knowledge, future arrays of many underwater turbines and multiple use of oceans within social ecological systems to maintain the conservation of marine biodiversity.